Neural correlates of attentional capture by stimuli previously associated with social reward. Issue 1 (2nd April 2020) - Kim, Andy J.; Anderson, Brian A.
ABSTRACT: Our attention is strongly influenced by reward learning. Stimuli previously associated with monetary reward have been shown to automatically capture attention in both behavioral and neurophysiological studies. Stimuli previously associated with positive social feedback similarly capture attention; however, it is unknown whether such social facilitation of attention relies on similar or dissociable neural systems. Here, we used the value-driven attentional capture paradigm in an fMRI study to identify the neural correlates of attention to stimuli previously associated with social reward. The results reveal learning-dependent priority signals in the contralateral visual cortex, posterior parietal cortex, and caudate tail, similar to studies using monetary reward. An additional priority signal was consistently evident in the right middle frontal gyrus (MFG). Our findings support the notion of a common neural mechanism for directing attention on the basis of selection history that generalizes across different types of reward.